Design of An Automatic Follower Shopping Trolley Based on Image Processing - Ananda, Gheri Febri; Wahyuni, Cici; Sania, Ellsa; Sukardi, Sukardi (Universitas Negeri Padang, 2019)
In the era of industrial revolution 4.0, all human activities are replaced by machines. Humans are required to optimize brain function than muscle function. All human work is facilitated by robots or tools work automatically. For example, shopping activities in the modern market. Consumers prefer to shop in the modern market than the traditional market, because the items are complete, neatly arranged, and they have facilities like trolleys as transporters. Trolleys can be pushed and pulled easily. But when shopping, parents have a problem with pushing or pulling a trolley when they carrying their children. Therefore, we created a design for automatic follower shopping trolley based on image processing which can follow the consumers when shopping. This trolley has a webcam camera as a sensor to take pictures of the objects or special accessories that used by consumers. The result of data are processed in such a way and then it will be obtained the x and y coordinates positions of the consumer and the next data will be sent to the Raspberry Pi 3 which will automatically determine the movement of the trolley. The test results showed that the distance range detected between trolleys and consumers ranged from 0.5 meters to 2 meters, and trolleys can move according to the point where the object was detected. Thus, the trolley can follow the user well.